Surface antigens from Escherichia coli O2 and O78 strains of avian origin. - Dho-Moulin, M (1990)
Fimbriae from O2 and O78 virulent strains of avian Escherichia coli were compared with type 1A fimbriae with regard to the apparent molecular weights of their subunits and their antigenic relationships. Under static broth culture conditions, most O78 strains expressed fimbriae closely related to those of type 1A. Under the same culture conditions, another type of fimbriae, sharing some common properties with type 1A fimbriae, was observed only on O2 strains; however, these fimbriae differed from type 1A fimbriae in the apparent molecular weights of their subunits and in the expression of specific epitopes. They were called type 1-like fimbriae. Homologies in lipopolysaccharide and outer membrane protein profiles were also demonstrated among the strains expressing type 1-like fimbriae, which suggests the existence of a clonal relationship among O2:K1 avian E. coli strains. The O78 strains studied did not appear to be clonally related.